2017
DOI: 10.12930/nacada-15-042
|View full text |Cite
|
Sign up to set email alerts
|

The Advising Palaver Hut: Case Study in West African Higher Education

Abstract: Although international research regarding advising is burgeoning, most of the research on the role of and advantages related to academic advising has been limited to U.S. colleges and universities. This ethnographic case study conducted at a Liberian university examined the organizational culture of advising from student, faculty, and staff perspectives after the establishment of the Student Academic Advisement and Career Counseling Center. The findings suggest two primary elements that shape the role of advis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our analysis revealed that of those that did report the sample's race (n ¼ 39), only six did not have majority white samples. Four of those six studies were focused on a particular non-white population, two of which were international studies conducted in Liberia and Hong Kong (Cheung et al, 2017;Sy, 2017). As a result, only four of the 85 total studies examined majority non-white samples in the United States.…”
Section: Rq2: Samples and Research Contextsmentioning
confidence: 99%
“…Our analysis revealed that of those that did report the sample's race (n ¼ 39), only six did not have majority white samples. Four of those six studies were focused on a particular non-white population, two of which were international studies conducted in Liberia and Hong Kong (Cheung et al, 2017;Sy, 2017). As a result, only four of the 85 total studies examined majority non-white samples in the United States.…”
Section: Rq2: Samples and Research Contextsmentioning
confidence: 99%